(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Electrospun nanofibers have increasingly attracted attention to be used as new generation tissue engineering scaffolds since they have the nanofibrous structure, which can biomimic the native Extracellular Matrix (ECM). This paper gives the review of our 10 years research on electrospun nanofibers for tissue engineering. Natural polymers like collagen and chitosan have been electrospun into complex nanofibers to biomimic the native ECM both in structure and components. Collagen-chitosan or silk fibroin (SF) was also blended with synthetic poly (L-lactide-co-ε-caprolactone) (P(LLA-CL)) and electrospun into collgen-chitosan-P (LLA-CL) nanofibers or SF-P(LLA-CL) nanofibers to achieve both good mechanical properties and biocompatibility. Coaxial electrospinning was used to encapsulate the biomolecules into nanofibers to display antithrombotic properties. The nanofiber scaffolds have been used for skin, nerve and blood vessel tissue engineering in vivo.